Exploring Factors Influencing Enrollment in Master’s in Population Education at Sanothimi Campus - Acharya, Milan (Spandan, 2023)
This study examines the factors affecting student enrollment in the Master's program in Population Education. The objective was to explore the causes of low enrollment and suggest strategies to encourage students to join the program. A qualitative research design with a case study approach was used. The study focused on students who completed a Bachelor’s degree in Population Education. Sanothimi Campus, Bhaktapur, was selected purposively as the sample campus as I am a teacher educator for the last eight years in this campus. Ten master's level students, two dropped-out students, the Head of the Health and Population department, and an assistant campus chief were interviewed using purposive sampling. Thematic analysis revealed key factors affecting enrollment, such as mandatory attendance policies, lack of motivation and interest, frequent assessments, and limited social respect for the teaching profession. The study recommends re-structuring the semester system to suit the Nepalese context, incorporating culturally relevant content, and enhancing the status of the teaching profession to increase enrollment. These findings provide valuable insights into addressing the challenges and improving student participation in Population Education at the Master's level.